Dysregulated NAMPT signaling underlines the immune-suppressive microenvironment in venous leg ulcers - Jiating Wang; Lei Guo; Yunxi Tao; Yunting Xiao; Yejing Huang; Ling Pan; Chen Lyu; Liping Zhu; Xiya Zhang; Juan Gao; Chunyan Cao; Zhuang Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Venous leg ulcers (VLUs) are the most common form of lower extremity ulceration, with a rising prevalence among the elderly. Despite their clinical significance, the molecular mechanisms underlying VLU remain poorly defined. In this study, we constructed a comprehensive single-cell transcriptional atlas of VLUs, unveiling a widespread immunosuppressive microenvironment within the lesions. Specifically, stromal cells exhibited attenuated inflammatory responses coupled with enhanced fibrotic activity. Keratinocytes and endothelial cells demonstrated increased proliferative and angiogenic activity, respectively, yet both cell types showed markedly reduced antigen-presenting capacity. Immune cell compartments displayed profound dysfunction characterized by marked reductions and impaired functionality of dendritic cells, polarization of macrophages toward an anti-inflammatory M2 phenotype, and enrichment of T cell exhaustion signatures. Notably, cell–cell communication analysis revealed diminished crosstalk between immune and structural cell populations. Mechanistically, we identified NAMPT-mediated signaling as a critical regulator of myeloid-stromal crosstalk. Targeted depletion of NAMPT in macrophages disrupted fibroblast-mediated inflammatory responses and impaired wound healing, whereas exogenous NAMPT administration reactivated immune responses and promoted tissue repair in chronic wounds. Collectively, these findings provide a comprehensive molecular framework for understanding immune–stromal dysfunction in VLUs and position NAMPT as a central immune regulator and promising therapeutic target for chronic wound treatment.